Nummer 1: Veldhuizen, 2: Jokel 3: Pot 4: Kol v. Bemmelen 5: Bakker 6: Stomps 7: Zwart 8: Van Lanschot (1946)
Nummer 1: Veldhuizen, 2: Jokel 3: Pot 4: Kol v. Bemmelen 5: Bakker 6: Stomps 7: Zwart 8: Van Lanschot.